2022
DOI: 10.1002/jdd.13030
|View full text |Cite
|
Sign up to set email alerts
|

Stress among dental students transitioning from remote learning to clinical training during coronavirus disease 2019 pandemic: A qualitative study

Abstract: Objectives To identify dental students’ perceptions of stress over returning to in‐person clinical training after remote learning required from the coronavirus disease 2019 (COVID‐19) pandemic. Methods This was a qualitative observational study. The sample was composed of undergraduate students ( n = 47) in the final year of São Paulo State University, School of Dentistry, Araraquara program. The data were collected using a questionnaire creat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 44 publications
0
9
0
Order By: Relevance
“…Specifically, as compared to those in the first tertile, those in the third tertile of vigilance and discrimination (i.e. high levels of heightened vigilance and perceived discrimination) had significantly higher mean anxiety (8.2 vs. 5.2; p = 0.0003 for vigilance and 8.5 vs. 4 p < 0.0001 for discrimination) scores. Similarly, those who reported that they were not too/not confident in entering clinical practice or residency also had higher mean anxiety (7.6 vs. 6.0; p = 0.03), perceived stress (17.9 vs. 16.2; p = 0.05), lower resilience (19.8 vs. 21.1; p = 0.03) and lower coping (37.9 vs. 39.5; p = 0.05) scores.…”
Section: Resultsmentioning
confidence: 91%
See 1 more Smart Citation
“…Specifically, as compared to those in the first tertile, those in the third tertile of vigilance and discrimination (i.e. high levels of heightened vigilance and perceived discrimination) had significantly higher mean anxiety (8.2 vs. 5.2; p = 0.0003 for vigilance and 8.5 vs. 4 p < 0.0001 for discrimination) scores. Similarly, those who reported that they were not too/not confident in entering clinical practice or residency also had higher mean anxiety (7.6 vs. 6.0; p = 0.03), perceived stress (17.9 vs. 16.2; p = 0.05), lower resilience (19.8 vs. 21.1; p = 0.03) and lower coping (37.9 vs. 39.5; p = 0.05) scores.…”
Section: Resultsmentioning
confidence: 91%
“…1,2 Dental trainees experienced anxiety and stress about personal safety, professional security, and the future of the dental profession amidst their increased risk of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) exposure, transmission, and infection due to the commonplaceness of airborne droplets and aerosols generated in dental care settings. 3 Some dental trainees, particularly those in pre-clinical years also found emergency remote learning to be inadequate preparation for in-person clinical instruction 4 further complicating the need the curb the spread of the virus and provide adequate training to students. Concurrently with the COVID-19 pandemic, dental trainees in the United States were also faced with the centuries-old pandemic of racism.…”
Section: Introductionmentioning
confidence: 99%
“…While the similarities in responses are promising, the main area of disagreement represents an important focal point for future calibration efforts. With dental students reporting higher than average stress levels regarding infection risks and inadequate hand skills entering practice during the COVID-19 pandemic, it is important now more than ever to create a supportive educational environment in which they can rely on instructors for guidance and confidence (Garcia et al, 2022). The consistent use of a survey similar to the one described in this study can be used as a tool to assess areas where clinical instruction can be improved.…”
Section: Discussionmentioning
confidence: 99%
“…The Discourse of the Collective Subject (DCS) is a qualitative data analysis method that uses collective thinking to explore the social work field and rescue the differences and similarities between the views of the participating subjects [15]. This analysis has been indicated when it is necessary to deepen the understanding of the behaviors of a specific group and was used in previous researches to evaluate dental students [17][18][19].…”
Section: Discussionmentioning
confidence: 99%